Atypical Neurological Manifestation in Childhood Microscopic Polyangiitis: A Case Report and Review of Literature - Suksai, Preawkalaya; Wasuanankun, Suphawe; Lekhavat, Vitit; Sirimongkolchaiyakul, Ornatcha; Tangcheewinsirikul, Sirikarn (Frontiers in Pediatrics, 2022)
Microscopic polyangiitis (MPA), a systemic necrotizing vasculitis of small vessels, is primarily associated with necrotizing and crescentic glomerulonephritis and pulmonary capillaritis. Neurological involvement, particularly of the central nervous system (CNS) is scarcely observed. The diversity of CNS symptoms could puzzle the diagnosis causing delays in treatment and potentially having a considerable effect on patient's quality of life or even death. The aim of this case report is to highlight the unusual manifestation of MPA in order to raise awareness of this orphaned disease among pediatricians or even pediatric rheumatologists and neurologists. Case Report Herein we report the case of a 13-year-old Thai girl diagnosed with MPA presented with rapidly progressive glomerulonephritis (RPGN). Renal biopsy was performed demonstrated crescentic glomerulonephritis with negative immunofluorescence and positive titer of myeloperoxidase (MPO) antibody. Pulse methylprednisolone (MP) and cyclophosphamide (CYC) as well as plasmapheresis were initiated. Despite treatment with prednisolone (45 mg/day) and monthly CYC for two doses, she experienced a brief generalized tonic–clonic seizure during the follow-up period. The potential differential diagnosis of new-onset neurological manifestation contains infection owing to the immunocompromised status of the patient and CNS vasculitis as a result of the disease itself. Lumbar puncture was performed, and cerebrospinal fluid analysis demonstrated pleocytosis with negative infectious panel. Contrast magnetic resonance imaging studies of the brain showed multifocal patchy T2/FLAIR-hyperintense lesions in the cerebral as well as cerebellum regions, and irregular narrowing along the V4 segment of the right vertebral artery was demonstrated in magnetic resonance angiography. In the presence of CNS vasculitis, pulse MP and CYC were provided. The symptom of nervous system has progressively improved. Conclusion In our case, MPA revealed RPGN with neurological manifestation. Despite the fact that it is scarcely reported, CNS vasculitis is one of the organ-threatening symptoms. To improve patient morbidity and mortality, multidisciplinary care teams with prompt diagnosis and treatment are highly recommended.